Podocyturia an emerging biomarker for kidney injury - Charbel Hanna; Hady El Etry; Maroun Ibrahim; Lynn Khalife; Sola Aoun Bahous; Wissam H. Faour (BMC Nephrology)
Abstract Podocyte injury is an established hallmark of kidney disease progression. Podocyte loss is a widely proven hypothesis to explain, in part, glomerular damage. Regardless of the underlying kidney disease, the pathophysiologic processes frequently involve the glomerulus. A growing body of evidence considered that podocytes detachment (podocytopathy) and their presence in the urine (podocyturia) are the hallmark of glomerular disease progression. As such, developing new tools to monitor disease progression non-invasively is of major clinical importance. Detection of podocytes in the urine as a biomarker of disease progression would be a major achievement toward the development of such tools. This review summarizes current knowledge about podocyturia.